Management of toxicities associated with novel immunotherapy agents in acute lymphoblastic leukemia - Jain, Tania (Ther Adv Hematol, 2020)
The advent of novel immunotherapies, such as blinatumomab, inotuzumab, and chimeric antigen receptor (CAR) T cell therapy, has revolutionized the therapeutic landscape in the treatment of relapsed/refractory B cell acute lymphoblastic leukemia, but can be associated with specific toxicities. We review unique toxicities of each of these in this article. Blinatumomab, a bispecific T cell engager, has been associated with cytokine release syndrome (CRS) and neurological toxicities, both of which can be prevented and managed with corticosteroids. Inotuzumab is a calicheamicin-conjugated CD22 targeting antibody. The calicheamicin component of the drug is likely associated with the hepatotoxicity seen with inotuzumab, especially sinusoidal obstruction syndrome, which can happen both in the context of the drug alone, and also with allogeneic stem cell transplantation. QT prolongation has also been noted with inotuzumab. CAR T therapy uses genetically modified autologous T cells directed against CD19, a known target on B cells. CRS and neurological symptoms, formally termed as immune-effector-cell-associated neurological syndrome, have been described along with hypogammaglobulinemia, cytopenias, and infections.